Characterization of Avian Encephalomyelitis Outbreaks Occurred in South Korea from 2006 to 2013 - Hye-Ryoung Kim; Yong-Kuk Kwon; Hee-Soo Lee (The Journal of Poultry Science, 2015)
This study was conducted to characterize avian encephalomyelitis (AE) viruses obtained from various flocks of breeder and commercial chickens in South Korea. Young chicken less than 4 weeks old showed neurological sign were diagnosed as typical AE infection between 2006 and 2011. In 2013, idiopathic AE occurred on the unvaccinated 79 day-old chickens that had clinical signs of ataxia and paralysis. Phylogenetic analysis of viral protein 2 genes of AE viruses showed that all AE field viruses tested were genetically similar to vaccine strain [Calnek 1143]. In the embryo-inoculation test via the yolk sac, only one field strain and one commercial vaccine were embryo-adapted. The results indicated that the AE outbreaks in South Korea were caused by strains genetically similar to vaccine strain indicating possibility of vaccine breakdown or persistence in the chicken population.